Resplittable threshold multi-broker proxy re-encryption scheme from lattices - Ju-yan LI; Chun-guang MA; Qian ZHAO (Tongxin xuebao)
Two different encryption schemes and Lagrange polynomial were used to construct a resplittable threshold multi-broker proxy re-encryption scheme on the lattice,namely the encryption in the ciphertext input and output side was different from the encryption in the re-encryption side which make the bound of noise was more relaxed.Threshold multi proxy not only ensure the safety of re-encryption key,but also ensure re-encryption scheme can still work even if the individual proxy could not provide normal services.The scheme is proven IND-UniRTPRE-CPA secure.